Chinese cross-border mergers and acquisitions: How communication practices impact integration outcomes - Jean Wang; Lars Schweizer (Thunderbird International Business Review, 2023)
This study provides an empirical investigation on how communication practices impact the post-acquisition integration outcomes, in the context of Chinese cross-border mergers and acquisitions (CBMAs). We tailored our assessment to reflect communication practices during Chinese CBMA integration. The integration outcomes are measured by organizational commitment and strategic performance improvement. Using a data collected via survey from global executives and middle managers, we find that communication accuracy, channel efficiency, and overseas business management department positively impact organizational commitment. Moreover, inter-organizational trust mediates the effect of communication accuracy on organizational commitment, and communication officer on organizational commitment. In addition, we find that the language barrier of the Chairman negatively impacts strategic performance improvement. Moreover, acquisition experience, business relatedness, industrial investors, private-owned investors, and management consultant all positively affect strategic performance improvement. However, middle managers negatively impact the integration outcomes.
Keywords: 330; Chinese CBMA integration outcomes; communication; communication expediters; inter-organizational trust; language barrier; PLS-SEM